Clinical evaluation of Morgellons disease in a cohort of North American patients - Melissa C. Fesler; Marianne J. Middelveen; Raphael B. Stricker (PAGEPress Publications, 2018)
Morgellons disease (MD) is a dermatological condition characterized by aberrant production of keratin and collagen fibers in skin. Although infection with Borrelia burgdorferi, the causative agent of Lyme disease (LD), has been associated with MD, relatively few studies have hitherto provided epidemiological evidence regarding this association. A cohort of 1000 seropositive North American LD patients was evaluated for the presence of MD. Patients were diagnosed with MD based on detection of microscopic fibers in skin lesions or under unbroken skin. Demographic and clinical features of MD patients were analyzed, and laboratory testing for tickborne coinfections and other infectious agents, was performed. Subjective and objective features of MD were analyzed using statistical methods. Of 1000 seropositive LD patients, 60 (6%) were diagnosed with MD. Of these 60 patients, 75% were female and 78% presented in the late disseminated stage of MD. All 60 patients (100%) were seropositive for B. burgdorferi infection. Tickborne coinfections in these patients included Babesia spp (62%), Bartonella and Rickettsia (25% each), Ehrlichia (15%) and i (10%). Helicobacter pylori was detected in 12% of MD patients. In all, 77% of MD patients had one or more coinfections. This study confirms recent findings that MD occurs in a limited subset of LD patients. The clinical and genetic determinants of MD in LD patients require further study.